Chilton Chrysler service manual (Thomson/Delmar Learning, 2008)
Engine removal to drive train components to brake systems is covered in nine sections, which include: Complete service specs incl: tune-up, capacities, valve, piston and ring, brake, torque and wheel alignment; replacement procedures for virtually every major component; and year, model and engine id. 100s of drawings, exploded views and specs supplement the coverage of virtually every major operating system of Chrysler cars, light trucks and vans. Notes and cautions highlight the text for safe, error-free repairs. Shrink Wrapped & NOS